SISTEM PROTEKSI PADA PESAWAT BOEING 737 – CLASSIC: Retno Aita Diantari, Shulli Alifiannisa Putri - Jurnal, Redaksi Tim (ENERGI & KELISTRIKAN, 2019)
Boeing 737 requires a mains voltage of 115 volts AC, 28 volt AC and 28 volts DC to operate. The voltage obtained from various sources of electrical energy. The main source of electrical energy are two generator that produces AC voltage of 115 volts, 400 Hz. Electrical protection system on the aircraft is made to the security system of electrical equipment installed in the power system in the aircraft. The purpose of the protection system is to prevent damage to electrical equipment due to disturbances such as over current, under-voltage, high voltage, over frequency, under frequency, and differential current. In addition, to reduce the number of accidents due to aircraft electrical equipment always gated. For the control and safety on aircraft electrical system own Generator Control Unit (GCU) and Bus Protection Panel (BPP) with different functions. Electrical installation on aircraft designed for air still have power even though in a state of emergency, in order to keep operating safely and comfortably.